Efficient CRDT Synchronization at Scale using a Causal Multicast over a Virtual Hypercube Overlay - Galesky, Leonardo de Freitas; Rodrigues, Luiz Antonio (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2022: Companion Proceedings of the 11th Latin-American Symposium on Dependable Computing, 2022)
This paper presents a work in progress that intends to evaluate the use of a virtual hypercube topology as a partial replication protocol for a data store based on Conflict-free Replicated Data Types (CRDT). CRDTs can ensure consistency in a deterministic and conflict-free manner. This project presents a review of recent solutions for the replication of CRDTs, and proposes the input data and the test environment for evaluation. Currently, we are focused on building a prototype based on the VCube-PS pub-sub protocol. Various load and network distributions will be later evaluated using the Grid5000 testbed. The results will be compared with other replication protocols proposed in recent research to determine the feasibility of the proposed specification in terms of latency, scalability, and fault tolerance.